Leptospiral protein LIC11334 display an immunogenic peptide KNSMP01. (December 2020) - Prasad, Muthu; Bothammal, Palanisamy; Akino Mercy, Charles Solomon; Sumaiya, Krishnamoorthi; Saranya, Perumal; Muralitharan, Gangatharan; Natarajaseenivasan, Kalimuthusamy
Abstract: Leptospirosis is considered as a neglected tropical disease which is caused by pathogenic Leptospira spp. The precise mechanisms of leptospirosis pathogenesis are unclear and hence, the progress in development of treatment modalities has been dismal. The present study aimed to identify novel virulent factors of leptospires to understand the disease pathogenesis and to develop treatment modalities. Leptospira interrogans contains two chromosomes and encodes for ~3703 genes, but the functions of several open reading frames have not yet been explored. Among them, novel virulent associated leptospiral proteins (LIC11334, LIC11542, LIC11436, LIC11120 and LIC12539) were identified using VirulentPredict and the antigenicity of these targets was explored by VaxiJen server. Domain architecture of the pathogen specific proteins revealed that LIC11334 had potential to evoke significant immune response against leptospiral infection and LIC11436 contains four folds of immunoglobulin-like domain and plays a vital role in pathogenesis. Therefore, B-cell epitopes were predicted and the epitope of high virulence (and VaxiJen score from LIC11334) was chemically synthesized as peptide (KNSMP01) and labeled with Biotin (Biotin-SGSGEVENPDPKVAQEC). Binding affinity of KNSMP01 with MHC molecules was predicted and the molecule was discovered to have potential to elicit both humoral and cell mediated immune responses and found to interact with host components via hydrophobic interaction, hydrogen bonding and salt bridges. Rabbit antisera was raised against KNSMP01 and found to elicit antigenicity using Western, ELISA and dot blot assays. In silico and in vitro experiments show KNSMP01 to be a promising immunogen and may be a better vaccine candidate for leptospirosis. Highlights: The functions of several open reading frames of Leptospira genome are undetermined. VirulentPredict and VaxiJen were used to explore the antigenic LIC11334 among them. Antigenic epitope of LIC11334 was chemically synthesized as peptide KNSMP01. Antisera of KNSMP01 found to elicit immunogenicity by Western, ELISA and dot blot assays. In silico and in vitro experiments show KNSMP01 to be a promising immunogen.